2013
DOI: 10.1016/j.surg.2013.04.064
|View full text |Cite
|
Sign up to set email alerts
|

Total thyroidectomy for Graves’ disease: Compliance with American Thyroid Association guidelines may not always be necessary

Abstract: Background Total thyroidectomy (TT) is the preferred surgical approach to Graves' disease (GD). Current American Thyroid Association (ATA) guidelines call for administration of potassium iodide (KI) and achievement of euthyroid state before operation. Small numbers and a mixture of surgical approaches spanning several decades hinder previous surgical series. We present the outcomes for TT at a single high-volume center. Methods A retrospective cohort study was conducted on 165 patients undergoing TT for GD f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 25 publications
3
34
1
Order By: Relevance
“…Even though defined slightly differently in the studies by Shinall and colleagues, their observed rates of transient hypoparathyroidism (27–31%) were comparable to the group of patients not prepared with KI (26%) in the current study and substantially higher than the rate in the group that did receive KI (7%). 16,17 These data suggest that the lack of a perceived benefit from KI administration in those studies is likely related to the limitations of the control groups rather than KI truly having no impact.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Even though defined slightly differently in the studies by Shinall and colleagues, their observed rates of transient hypoparathyroidism (27–31%) were comparable to the group of patients not prepared with KI (26%) in the current study and substantially higher than the rate in the group that did receive KI (7%). 16,17 These data suggest that the lack of a perceived benefit from KI administration in those studies is likely related to the limitations of the control groups rather than KI truly having no impact.…”
Section: Discussionmentioning
confidence: 90%
“…They concluded that pre-operative KI was not necessary. 16 In a separate study looking exclusively at patients with Graves’ disease, Shinall and colleagues 17 found that noncompliance with American Thyroid Association recommendations for the preoperative preparation of patients with Graves’ disease (which includes KI administration) was not associated with increased complications but their study cohort only included 3 patients who received KI preparation 17 . Even though defined slightly differently in the studies by Shinall and colleagues, their observed rates of transient hypoparathyroidism (27–31%) were comparable to the group of patients not prepared with KI (26%) in the current study and substantially higher than the rate in the group that did receive KI (7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No perioperative complications were observed, however, in 3 other studies of thyroidectomy in AIT (although in 1 of these, 71% of the patients were prepared for surgery using iopanoic acid) [8,9,11] . A recent retrospective analysis of 165 Graves disease patients who were treated with total thyroidectomy did not show a difference in surgery-related morbidity or mortality between the group that reached euthyroidism and the patients who still had hyperthyroidism (42%) preoperatively [12] . Nonetheless, TPE has been proposed as a safe and effective procedure for restoring euthyroidism and preparing patients for thyroidectomy in Graves disease, toxic multinodular goiter, and hyperthyroidism related to iodine excess [13,14] .…”
Section: Discussionmentioning
confidence: 94%
“…Small studies utilizing thyroid scans (3) or ultrasound (4,5) have demonstrated decreased thyroid blood flow and decreased blood loss (5) in Graves' disease patients treated with a short (7-10 days) course of Lugol's solution. Although an iodide preparation is often used, and is recommended by the ATA guidelines for this purpose, it is by no means a modern standard of care (6,7). Our surgical practice used SSKI sporadically for Graves' patients rendered euthyroid by modern medications, and uniformly performed either Total -or near TotalThyroidectomy for this condition.…”
Section: Introductionmentioning
confidence: 99%